Wives, Mothers, and the Red Menace : Conservative Women and the Crusade against Communism - Brennan, Mary C. (Book collections on Project MUSE., 2008)
"This book is clearly written, admirably concise, and well situated in the secondary literature on gender and conservatism and the foreign and domestic Cold War. ... Brennan's study offers another valuable reminder that niether Joe McCarthy nor June Cleaver can stand as convenient shorthard for our historical narratives of the Cold War era." Journal of American History.